HEDGES USED IN THE UNITED STATES PRESIDENTIAL SPEECHES - Kusumaningroem, Ismi; Rukmini, Dwi; Yuliasri, Issy (English Education Journal, 2015)
This study attempts to describe the used hedges in the United States Presidential Speeches. This study is intends to identify the types of hedges and the reason for choosing hedges in the Three United States Presidential Speeches by Salager-Meyerâs theory (1997). They are President Bill Clinton, George W Bush, and Barrack Obama. This study used qualitative descriptive approach the data collected by The Three Unites States Presidential Speech in inauguration speech result find out they are mostly used the types of hedges is approximates degree. They used approximate degree is to anticipate or minimize the mistake in starting confirmation in the proposition. Finally, the reasons choosing hedges in the three United States Presidential speechesgenerally used to show the confusion and vagueness. The point is the speaker may hope the strength of statement that should be claims and would not be justify by experimental data present, choosing instead to remain vague in their statement. In addition, in the three United States Presidential Speeches used few or less reasons choosing hedges to show the positive or negative positive politeness.